MANAJEMEN HUMAS LEMBAGA PENDIDIKAN DI ERA DIGITAL: STRATEGI MEMBANGUN CITRA DAN KEPERCAYAAN PUBLIK - Lutfan Sonʼany (STKIP Pesisir Selatan, 2026)
Objective: This study aims to explain the concept of public relations (PR) management of educational institutions in the digital era and to formulate digital PR strategies for building institutional image and public trust. Methods: This study used a qualitative approach with a descriptive-analytical library research design; data drawn from books, journal articles, and documents were analyzed through content analysis (data reduction, display, and conclusion drawing) supported by source triangulation. Results: The findings show that digital PR management rests on four main strategies, namely information transparency through official websites and online admission services, consistent social media management, responsive two-way communication, and partnership with the community and media. These strategies operate as an ongoing cycle of planning, publication, interaction, issue management, and evaluation, and together they build a positive image and public trust. Novelty: This study positions digital technology not merely as a learning tool but as a strategic means of building institutional image and public trust, an aspect still rarely examined in the educational management literature. The results are expected to serve as a practical reference for education managers in organizing digital communication in a more planned and inclusive manner.